Developing and Delivering Behavioral Interventions Through Telehealth. Issue 2 (March 2023) - Carroll, Regina; Halbur, Mary; Preas, Elizabeth
This special issue on telehealth in Behavior Modification features 10 studies related to developing and delivering behavioral interventions through telehealth. The studies in this issue cover a variety of topics including using telehealth to train caregivers, training clinicians to use telehealth, and directly implementing interventions or assessments through telehealth. The special issue concludes with a comprehensive literature review examining variables that impact the effectiveness of telehealth as a service-delivery tool.